Panglial gap junctions between astrocytes and olfactory ensheathing cells mediate transmission of Ca2+ transients and neurovascular coupling. Issue 7 (18th March 2019) - Beiersdorfer, Antonia; Scheller, Anja; Kirchhoff, Frank; Lohr, Christian
Abstract: Astrocytes are arranged in highly organized gap junction‐coupled networks, communicating via the propagation of Ca 2+ waves. Astrocytes are gap junction‐coupled not only to neighboring astrocytes, but also to oligodendrocytes, forming so‐called panglial syncytia. It is not known, however, whether glial cells in panglial syncytia transmit information using Ca 2+ signaling. We used confocal Ca 2+ imaging to study intercellular communication between astrocytes and olfactory ensheathing glial cells (OECs) in in‐toto preparations of the mouse olfactory bulb. Our results demonstrate that Ca 2+ transients in juxtaglomerular astrocytes, evoked by local photolysis of "caged" ATP and "caged" t ACPD, led to subsequent Ca 2+ responses in OECs. This transmission of Ca 2+ responses from astrocytes to OECs persisted in the presence of neuronal inhibition, but was absent when gap junctional coupling was suppressed with carbenoxolone. When Ca 2+ transients were directly evoked in OECs by puff application of DHPG, they resulted in delayed Ca 2+ responses in juxtaglomerular astrocytes, indicating that panglial transmission of Ca 2+ signals occurred in a bidirectional manner. In addition, panglial transmission of Ca 2+ signals from astrocytes to OECs resulted in vasoconstriction of OEC‐associated blood vessels in the olfactory nerve layer. Our results demonstrate functional transmission of Ca 2+ signals between different classes of glial cells within gap junction‐coupled panglial networks and the resulting regulation of blood vessel diameter in the olfactory bulb. Main Points: Astrocytes and olfactory ensheathing cells are coupled by gap junctions. Ca 2+ signals in astrocytes result in delayed Ca 2+ transients in olfactory ensheathing cells. Ca 2+ signals in OECs trigger vasoresponses in adjacent blood vessels. ‐ Ca 2+ signals in astrocytes result in delayed Ca 2+ transients in olfactory ensheathing cells. ‐ Ca 2+ signals in OECs trigger vasoresponses in adjacent blood vessels.